A study of the solvent effect on the crystal morphology of hexogen by means of molecular dynamics simulations. Issue 32 (10th April 2015) - Chen, Gang; Chen, Chunyu; Xia, Mingzhu; Lei, Wu; Wang, Fengyun; Gong, Xuedong
<x xml:space="preserve">Abstract</x> In this work, molecular dynamics simulations have been performed to study the solvent effect on the crystal morphology of hexogen.